Determinant Analysis of Residual Net Income in The Sharia Cooperative: Company Size as Mediator - Bulan Karima Nurani; Hasan Mukhibad (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2018)
This study aims to identify the effect of owner’s capital and financing to residual net income (SHU), and how its effect when mediated with total assets. The population in this research are all Sharia Cooperatives which operates in Semarang regency, there are 25 cooperatives. Sampling technique used was purposive sampling technique, which finally obtained 13 cooperatives with 5 years’ period of observation. The method of analysis used to answer the hypothesis in this research are Path Analysis and Sobel Test. The results of this study indicates that owner’s capital and financing have a significant positive effect on total asset, owner’s capital has significant positive effect on net income, financing has no significant effect on net income, total asset has insignificant positive effect on net income, total asset did not succeed in mediating the effect of owner’s capital on net income, and total asset succeed in mediating the effect of financing on net income.